Representasi Nilai Kenabian dalam Antologi Puisi Rumah-Mu Tumbuh di Hati Kami Karya Sosiawan Leak: Tinjauan Sastra Profetik - Agus Tika Dwi Savira; Siti Isnaniah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research was motivated by the problem of the inequality of the principle of 'Tibak Rasul' between the previous generations of prophets and the present generation, which is in the anthology book of poetry Rumah-Mu Tumbuh di Hati Kami by Sosiawan Leak. The objectives of this study are (1) to find out how the representation of prophetic values ​​in the poetry anthology entitled Rumah-Mu Tumbuh di Hati Kami by Sosiawan Leak, (2) to find out how it is implemented in learning Indonesian Language and Literature at Madrasah Aliyah. This study used a qualitative descriptive method, while the analysis knife applied was structuralism. The meaning is then described and analyzed using a prophetic literature review based on the theory presented by Kuntowijoyo in his book entitled Maklumat Sastra Prophetic. This type of research is a research library. The primary data source used is the anthology book by Sosiawan Leak, entitled Your house grows in our hearts. Reference sources used are in the form of books, journals, e-books, theses, theses, and articles that support and support research problems. The data collection technique used was content analysis, namely listen, read, and take notes. The results of this study indicate that there are (1) prophetic values ​​contained in the poetry anthology Rumah-Mu Tumbuh di Hati Kami, including humanization consisting of 4 data, transcendence of 7 data, and liberation of 2 data. (2) Implementation in learning Indonesian Language and Literature at Madrasah Aliyah.